Mass Multiplication of Arbuscular Mycorrhizal Fungus Glomus intraradices Through Root Organ Culture - (:unkn) unknown (Dharwad, 2023)
An investigation was carried out to mass multiply Glomus intraradices by newlineAgrobacterium rhizogenes (MTCC-532) induced chickpea hairy roots through Halfclosed newlineAutotrophic Mycorrhizal-Plant (HAM-P) system. Among the different methods newlineexploited for the hairy root initiation in chickpea seedling, the method comprised of newlinecutting the radicle followed by smearing with broth containing cells of A. rhizogenes newlinerecorded the maximum degree of hairy root initiation at 15 DAI (22.33), followed with newlinedipping in A. rhizogenes (20.33). Further, the hairy roots were colonized with spores of newlineGlomus intraradices under HAM-P system resulted in spore germination, hyphal newlinebranching and daughter spore formation (1091 spores/plate) at 30 DAI. The mycorrhizal newlinecolonized hairy roots were collected from the HAM-P system and subjected for newlinelyophilization in order to develop a newer formulation. The infective propagules in the newlinelyophilized product were found to 16 x 103 IP g-1 of final product. Furthermore, a blend newlineof mycorrhizal infective propagules with a range of six carrier materials viz., lignite, talc, newlinehumic acid, glycerol, encapsulation and sodium alginate were evaluated for their newlineeffectiveness in delivering the formulations. Among the formulations, sodium alginate newlinebits with lyophilized AMF product recorded significantly the highest plant height (86.6 newlinecm), dry matter (89.94 g plant-1), AMF spore load (81.50 spores/50 g of soil), percent newlineroot colonization (61.33 %), dehydrogenase activity (5.12 and#956;g TPF formed g-1 soil d-1), newlinePhosphatase activity (16.04 and#956;g pnp released g-1 soil h-1), P content (0.56 %), P uptake newline(0.50 %) and plant physiological parameters viz., relative chlorophyll content, stomatal newlineconductance, photosynthetic rate were recorded maximum in sodium alginate bits with newlineAMF product over uninoculated control. Transpiration rate and leaf temperature newlinerecorded minimum over uninoculated control. Thus, our preliminary investigation newlineforms a basis for the production of monoexnic spore culture with an increased newlinesporulation over a short period
Keywords: Agricultural Sciences; Agriculture Multidisciplinary; Life Sciences; Mass Multiplication